Removal of Fluoride from Drinking Water Using Modified Immobilized Activated Alumina - Aneeza Rafique; M. Ali Awan; Ayesha Wasti; Ishtiaq A. Qazi; Muhammad Arshad (Journal of Chemistry)
The study describes the removal of fluoride from drinking water using modified immobilized activated alumina (MIAA) prepared by sol-gel method. The modification was done by adding a specific amount of alum during the sol formation step. The fluoride removal efficiency of MIAA was 1.35 times higher as compared to normal immobilized activated alumina. A batch adsorption study was performed as a function of adsorbent dose, contact time, stirring rate, and initial fluoride concentration. More than 90% removal of fluoride was achieved within 60 minutes of contact time. The adsorption potential of MIAA was compared with activated charcoal which showed that the removal efficiency was about 10% more than the activated charcoal. Both the Langmuir and Freundlich adsorption isotherms fitted well for the fluoride adsorption on MIAA with the regression coefficient R2 of 0.99 and 0.98, respectively. MIAA can both be regenerated thermally and chemically. Adsorption experiments using MIAA were employed on real drinking water samples from a fluoride affected area. The study showed that modified immobilized activated alumina is an effective adsorbent for fluoride removal.